Identifying Chronic Disease Risk Behaviors: An ontology-based approach - Pfeiffer Salomão Dias, Lucas; Damasceno Vianna, Henrique; Heckler, Wesllei; Luis Victória Barbosa, Jorge (iSys - Journal of Information Systems, 2024)
Chronic diseases are among the leading causes of death worldwide. Risk factors related to chronic diseases are correlated with people's lifestyles, and early changes can prevent many chronic disease deaths. This article proposes an ontology called B-Track Onto to classify behaviors that attenuate or worsen the risk factors associated with chronic diseases. The MIMIC-III dataset was used as the base to import 21 patients from the clinical samples. B-Track Onto inferred all imported patients and categorized them in the expected classes. Besides, this work executed SPARQL queries to answer the competence questions, which returned the expected results for each question. Furthermore, there was an evaluation of the ontology with 10 patients over 4 weeks, showing the ontology's ability to infer behaviors related to risk factors for chronic diseases during the patients' daily lives. This evaluation allowed the inference of patients' preventive and non-preventive habits related to chronic diseases. B-Track Onto is an ontology to correlate human behavior and risk factors of chronic diseases, being a potential tool for classifying preventive and non-preventive behaviors and mitigating chronic diseases.